Gut virome dysbiosis impairs antitumor immunity and reduces 5-fluorouracil treatment efficacy for colorectal cancer - Huang, Hui; Yang, Ying; Wang, Xiaojiao; Wen, Biao; Yang, Xianglan; Zhong, Wei; Wang, Qiurong; He, Feng; Li, Jun (Frontiers in Oncology, 2024)
IntroductionDespite the established influence of gut bacteria, the role of the gut virome in modulating colorectal cancer (CRC) patient chemotherapy response remains poorly understood. In this study, we investigated the impact of antiviral (AV) drug-induced gut virome dysbiosis on the efficacy of 5-FU in CRC treatment.MethodsUsing a subcutaneous CRC mouse model, we assessed tumor growth and immune responses following AV treatment, fecal microbiota transplantation (FMT), and 5-FU administration.ResultsAV therapy reduced the abundance of gut DNA and RNA viruses, leading to accelerated tumor growth, shortened survival, and diminished chemotherapy efficacy. FMT restored the gut virome, improving tumor suppression and extending the survival of 5-FU-treated mice. Metagenomic sequencing revealed significant changes in virome composition, AV treatment expanded Kahnovirus, Petivirales, and Enterogokushovirus, whereas FMT enriched Peduovirus STYP1, Mahlunavirus rarus, and Jouyvirus ev207. AV treatment reduced the number of dendritic cells and CD8+ T cells in peripheral blood and tumor tissues, impairing antitumor immunity, FMT reversed these deficiencies. To further investigate the underlying mechanisms, we examined the TLR3-IRF3-IFN-β pathway, essential for recognizing viral RNA and triggering immune responses. AV treatment downregulated this pathway, impairing immune cell recruitment and reducing chemotherapy efficacy, while activation of TLR3 with Poly(I:C) restored pathway function and enhanced the effectiveness of 5-FU.DiscussionThese findings suggest the importance of maintaining gut virome integrity or activating TLR3 as adjunct strategies to enhance chemotherapy outcomes in CRC patients.